Trade liberalization and spatial inequality: A methodological innovation in Vietnamese perspective - Henning Tarp Jensen; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
In this paper we calibrate two static computable general equilibrium (CGE) models with respectively 16 and 5,999 representative households. Aggregated and disaggregated household categories are consistently embedded in a 2000 social accounting matrix for Vietnam, mapping on a one-to-one basis to each other. Distinct differences in poverty assessments emerge when the impact of trade liberalization is analyzed in the two models. This highlights the importance of modeling micro household behavior and related income and expenditure distributions endogenously within a static CGE model framework. Our simulations indicate that poverty will rise following a revenue-neutral lowering of trade taxes. This is interpreted as a worst case scenario, which suggests that government should be proactive in combining trade liberalization measures with a pro-poor fiscal response to avoid increasing poverty in the short to medium term. – poverty ; trade liberalization ; general equilibrium models ; Vietnam
Keywords: D58; I32; O53; 330; Armut; Räumliche Verteilung; Außenhandelsliberalisierung; Allgemeines Gleichgewicht; Vietnam; CGE-Modelling